(untitled) (Transport systems and technologies, 2018)
The Article considers the possibility of application of situational - heuristic method (SHMC) for the construction of the model process of operative planning of loading-unloading works at the railway transportation. Under the estimate that settles accounts by means of SHMC, the steady level of implementation of one or another indexes attained by an object is thought of as situation that has been risen under the target period. The great number of unforeseeable processes and operations takes place at the construction of optimal plan of operating work, where the terms of implementation constantly change. Authenticity of prognosis depends on exactness of their determination. Therefore it is possible to use average technological norms for the operative planning. However, for every technological process it is expedient to educe the list of its affecting factors, and to build a prognosis taking into account their influence in every specific situation. A method is implemented by the complex of steps that use the accumulated knowledge with an operative situation taken into account in the region of road. Three stages of calculations are envisaged: preparatory, operative and self- learning. At the preparatory stage, we determine the list of influencing factors for each calculated sizes and draw up algorithms for their calculation. At the operational stage, we select data with the closest situations to the initial for the calculation of each forecast indicator of corteges of array of experience. The self-learning stage allows you to adjust the calculated sizes after receiving the current data. Built with the use of SHMC a programmatic project is exploited in the department of planning of transportations and organization of freight work of service of transportations of regional branch ―Yuzhnaya railway‖.